Novice and Experienced Teachers’ Perspectives: Multifactor Challenges in HOTS Implementation - Nais Saraswati; Mbarep Wicaksono (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2023)
The integration of High-Order Thinking Skills (HOTS) in language learning presents numerous opportunities to foster deeper learning. When it comes to integrating HOTS in the classroom, teachers confront a long list of problems. The purpose of this study was to investigate the potential difficulties that may arise during the implementation process. Employing a qualitative method, this study collected data by inviting one novice and one experienced EFL teachers teaching in junior high schools from two different regions in South Sumatra province. Interviews were conducted with participants using a semi-structured style in order to gather information regarding the challenges they encountered when attempting to include higher order thinking processes into learning activities. Following that, records pertaining to lesson plans and classroom observations were utilized as supporting data. The method of narrative inquiry was utilized in order to analyze the data. According to the result of the study, inadequate instructional media, teachers' misconceptions of HOTS, students' low English proficiency, inferior reading literacy level, and appalling learning motivation were the problems that were shown to be associated with the implementation of higher-order thinking.